The Application Potential and Advance of Mesenchymal Stem Cell-Derived Exosomes in Myocardial Infarction - Xianyun Wang; Yida Tang; Zhao Liu; Yajuan Yin; Quanhai Li; Gang Liu; Baoyong Yan (Hindawi Limited, 2021)
Myocardial infarction (MI) is a devastating disease with high morbidity and mortality caused by the irreversible loss of functional cardiomyocytes and heart failure (HF) due to the restricted blood supply. Mesenchymal stem cells (MSCs) have been emerging as lead candidates to treat MI and subsequent HF mainly through secreting multitudinous factors of which exosomes act as the most effective constituent to boost the repair of heart function through carrying noncoding RNAs and proteins. Given the advantages of higher stability in the circulation, lower toxicity, and controllable transplantation dosage, exosomes have been described as a wonderful and promising cell-free treatment method in cardiovascular disease. Nowadays, MSC-derived exosomes have been proposed as a promising therapeutic approach to improve cardiac function and reverse heart remodeling. However, exosomes' lack of modification cannot result in desired therapeutic effect. Hence, optimized exosomes can be developed via various engineering methods such as pharmacological compound preconditioned MSCs, genetically modified MSCs, or miRNA-loaded exosomes and peptide tagged exosomes to improve the targeting and therapeutic effects of exosomes. The biological characteristics, therapeutic potential, and optimizing strategy of exosomes will be described in our review.